Demographic Challenges and Their Impact on Economic and Social Stability in China - Huang Wei Thung; Lefevre, Louis; Hua, Chen Wei; Ming, Liu; Lin, Zhao Jie (Journal of Humanities and Social Sciences (JHASS), 2024)
China is facing a profound demographic shift characterized by declining birth rates, a rapidly aging population, and significant urban-rural disparities. Despite phasing out the one-child policy in 2015 and introducing two-child and three-child policies, the total fertility rate (TFR) fell below 1.0 in 2024, far below the replacement level of 2.1. These trends have led to negative population growth and a rising dependency ratio, projected to reach 60.3% by 2024. This demographic imbalance exacerbates labor shortages, increases labor costs, and places immense strain on healthcare and pension systems, particularly in rural areas where social service access remains inadequate. While similar challenges are evident in aging societies like Japan and South Korea, China’s regional disparities and economic scale complicate policy implementation. This study identifies gaps in addressing the structural challenges hindering fertility policies, including economic pressures, cultural resistance, and inequities between urban and rural regions. Employing secondary data analysis, trend analysis, and comparative case studies, this research evaluates demographic trends from 2020 to 2024 and assesses the effectiveness of current policies. Findings reveal the limited success of China’s pronatalist policies and underscore the urgent need for comprehensive reforms. Recommendations include targeted investments in rural areas, affordable childcare, gender-equitable policies, and technological adoption to mitigate labor shortages. Future research should explore global lessons, public attitudes, and innovative strategies to address the socio-economic implications of demographic shifts, offering insights for sustainable policy design in aging societies.